Manajemen Strategi Rekruitmen Kepala Madrasah Yang Responsif Gender di Lingkungan Kementerian Agama RI - Hesti Kusumaningrum; Kastolan Kastolan (Jurnal Ilmiah Wahana Pendidikan, 2022)
Achieving success in recruiting teachers and leaders is more than just filling job openings. It's about recruiting the best teachers and leaders, developing and retaining them. In the words of Nelson Mandela, "Education is a big engine of personal development". One of the priorities of the Strategic Plan of the Ministry of Religion in improving the quality of Islamic Education is improving the quality of learning through improving the quality of teachers. Improving the quality of teachers in madrasas is carried out through the Continuing Professional Development Program scheme. (PKB). One important component of the implementation of the PKB program for madrasah teachers is the important role of madrasa leadership in this case is the Madrasah Head. Several things can be done in the recruitment of Madrahan Principals, namely: providing training which is expected to provide opportunities for school coconuts and prospective principals to improve their competence, providing incentives, especially in rural areas with poor transportation access, and providing quotas or opportunities for female teachers to gain access to become leaders in madrasah.